2022
DOI: 10.3390/foods11203273
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insight into the Formation of Odour—Active Compounds in Sea Buckthorn Wine and Distilled Liquor Based on GC–MS and E–Nose Analysis

Abstract: Sea buckthorn wine (SW) and distilled liquor (DL) are fruit wines with beneficial health effects. However, their unpleasant flavour limits their development and widespread acceptance. Therefore, it is necessary to analyse their flavour composition and changes. In this study, differential metabolites of sea buckthorn DL during processing were analysed, and the relationships between E–nose sensor values and key volatile organic compounds (VOCs) were established. The results show that 133 VOCs were identified, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The antioxidant capacity is closely linked to the vitamin C content present in sea buckthorn wine ( 88 ). After fermentation, the antioxidant activity of sea buckthorn juice increased significantly, the free radical scavenging rate increased to more than 90%, and the levels of phenolic and flavonoid active substances also increased significantly in the early stage of fermentation ( 89 ).…”
Section: Applicationmentioning
confidence: 99%
“…The antioxidant capacity is closely linked to the vitamin C content present in sea buckthorn wine ( 88 ). After fermentation, the antioxidant activity of sea buckthorn juice increased significantly, the free radical scavenging rate increased to more than 90%, and the levels of phenolic and flavonoid active substances also increased significantly in the early stage of fermentation ( 89 ).…”
Section: Applicationmentioning
confidence: 99%
“…Therefore, the integrated analysis of E-nose and GC–MS data is crucial for comprehensively analyzing aroma characteristics and volatile compounds. By analyzing the distinct metabolites of sea buckthorn wine and distilled liquor, the correlation between key volatile components and E-nose sensors was established ( Xia et al, 2022 ). The results indicated that a positive correlation between seven sensors and alcohols and three sensors exhibited a positive correlation with acids, which demonstrated that the E-nose can differentiate sea buckthorn wine and distilled liquor based on their volatile components and detect trends in major aroma compounds rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…Various products can be processed from sea buckthorn. Not only can it be used in making dried sea buckthorn pulp [15], sea buckthorn beverage [16], and sea buckthorn freeze-dried powder [17] but it can also be made into sea buckthorn wine [18] and sea buckthorn oil [19], among other products. Sea buckthorn oil contains a number of pharmacological properties, including the ability to protect cardiovascular and cerebral vessels, improve circulation, and boost immunity.…”
Section: Introductionmentioning
confidence: 99%